2023
DOI: 10.3389/fnut.2023.1068343
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 fatty acids on alcohol-induced damage

Abstract: Alcohol is the most widely consumed psychoactive substance in the world that has a severe impact on many organs and bodily systems, particularly the liver and nervous system. Alcohol use during pregnancy roots long-lasting changes in the newborns and during adolescence has long-term detrimental effects especially on the brain. The brain contains docosahexaenoic acid (DHA), a major omega-3 (n-3) fatty acid (FA) that makes up cell membranes and influences membrane-associated protein function, cell signaling, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Therefore, omega-3 supplementation can have very positive effects in improving many pathological conditions, especially those caused by oxidative stress [21]. Good evidence exists that omega-3 supplementation ameliorated the ethanol-induced damage of different organs [7]. In our study treatment with ω-3 fatty acids normalized SOD activity in animals of the ethanol+ω-3 group.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Therefore, omega-3 supplementation can have very positive effects in improving many pathological conditions, especially those caused by oxidative stress [21]. Good evidence exists that omega-3 supplementation ameliorated the ethanol-induced damage of different organs [7]. In our study treatment with ω-3 fatty acids normalized SOD activity in animals of the ethanol+ω-3 group.…”
Section: Discussionsupporting
confidence: 52%
“…Living organisms protect themselves against oxidative damage by means of the enzymatic and non-enzymatic antioxidant defense systems. Catalase (CAT), SOD, and GSH-Px are among the most effective enzymatic antioxidant defense system [7]. Macit et al found a significant decrease in the activity of SOD and GSH-PX in the hippocampal tissue of rats exposed to chronic ethanol treatment [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHA and AA are major phospholipid components of brain cell membranes [16,19]. EtOH reduces DHA in the brain [20,21] and its deficit impacts on both cell membranes, altering their biophysical properties, and related membrane proteins, such as enzymes and receptors [19].…”
Section: N-3 Recovers Cb 1 Receptor Expression In the Brainmentioning
confidence: 99%
“…DHA and EPA are n-3 PUFAs that accumulate in brain cell membranes and maintain their structure and fluidity, restore glutathione levels, are anti-inflammatory, reduce oxidative stress and apoptosis, and overcome synaptic plasticity deficits, improving the cognitive impairment caused by prenatal EtOH exposure [16][17][18][19]. DHA is unevenly distributed among brain regions and between neurons and glial cells, and participates in membraneassociated protein functions, cellular signaling, gene expression, lipogenesis, neurogenesis and synaptic pruning [16].…”
Section: Introductionmentioning
confidence: 99%